(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2021)
Purpose: This paper aims to develop and validate the scale for measuring digital marketing orientation (DMO) in the hotel industry. Methodology: The robust exploratory and confirmatory factor analysis procedure is applied to a data set collected through an online survey of 164 hotels in Bosnia and Herzegovina, Croatia, Serbia, and Montenegro. Results: Digital marketing orientation has been conceptualized, and a scale has been developed to measure this construct. The scale consists of 15 items in three defined dimensions (subscales): Strategic emphasis, Digital intelligence generation, and Planning and resource provisioning. Conclusion: Using the developed digital marketing orientation (DMO) scale, hotel managers can conduct a DMO audit similar to conducting a market orientation audit to determine in which areas it is necessary to improve market orientation in the online environment. Academics may use the DMO scale to investigate its antecedents and the influence of other factors on DMO and/or the influence of DMO on other factors. This is the first study, to the author’s knowledge, that developed and validated a measurement scale for digital marketing orientation in the hotel industry.